2015
DOI: 10.1891/1945-8959.14.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Between Inclusion and Participation: Young Carers Who Are Absent From School

Abstract: In discussions of inclusion and exclusion, one often-neglected group at high risk of exclusion is that of school absentees. Researchers and the public normally focus on truants and school refusers, whereas students absent from school to take care of family members, or young carers, have received little attention so far. Because of the multicausal factors and extensive impacts of the phenomenon, research on both school absentees and young carers suggests a need for interdisciplinary approaches. Yet, these appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
1
18
0
2
Order By: Relevance
“…For example, Cluver et al (2013) showed that children in sub-Saharan Africa who look after parents with AIDS are at greater risk themselves of pulmonary tuberculosis. Second, a wide range of qualitative studies have shown that young carers and young adult carers may experience various economic and social disadvantages and difficulties, including restricted educational opportunities and employment (e.g., Kaiser and Schulze 2015), difficulties in meeting the demands on them in university education (e.g., Kettell 2018), reduced social capital (e.g., Barry 2011), and experience of stigma leading to secrecy and social withdrawal (e.g., Bolas et al 2007). Metzing-Blau and Schnepp (2008) found that families turn to secrecy as a means to keep the family together as it is felt to be under threat, thus the disadvantages can become compounded.…”
Section: Prevalence and Effects Of Caringmentioning
confidence: 99%
“…For example, Cluver et al (2013) showed that children in sub-Saharan Africa who look after parents with AIDS are at greater risk themselves of pulmonary tuberculosis. Second, a wide range of qualitative studies have shown that young carers and young adult carers may experience various economic and social disadvantages and difficulties, including restricted educational opportunities and employment (e.g., Kaiser and Schulze 2015), difficulties in meeting the demands on them in university education (e.g., Kettell 2018), reduced social capital (e.g., Barry 2011), and experience of stigma leading to secrecy and social withdrawal (e.g., Bolas et al 2007). Metzing-Blau and Schnepp (2008) found that families turn to secrecy as a means to keep the family together as it is felt to be under threat, thus the disadvantages can become compounded.…”
Section: Prevalence and Effects Of Caringmentioning
confidence: 99%
“…Nevertheless, taking care of a family member can also have negative caregiving outcomes, especially for adolescents who have still to define a personal sense of identity, adopt a subjective value system, and re-negotiate relationships with parents as carers, during this developmental and transitional phase to adulthood [ 8 ]. A young caregiving role may indeed exacerbate the risk of experiencing mental health problems [ 38 ], health inequalities during the life course [ 5 , 12 , 39 , 40 ], poor well-being [ 41 , 42 ], restrictions in education and employment opportunities [ 43 , 44 ], as well as stigma leading to social isolation [ 45 ], frustration [ 35 ], and stress [ 25 ]. Furthermore, the recent Covid-19 pandemic, and the lockdown imposed by European governments as a response to the outbreak, had a dramatic impact on the mental health and well-being of family carers of all ages [ 46 ], and AYCs especially experienced a worsening of their mental health and social isolation [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kindern und Jugendlichen bereitet die Vereinbarung von familiären Pflegeaufgaben mit den Anforderungen der Schule Mühe, was zu einem Einbruch des Leistungsniveaus führen kann; dies kann wiederum Folgen für die zukünftige Entwicklung haben. Als weiteres Resultat der nicht-entwicklungsgerechten Übernahme von Pflegeverantwortung können körperliche wie auch psychische Probleme, Probleme in der Schule (Bullying) und Restriktionen in der Ausübung von Freizeitaktivitäten (Hobbys, Freunde treffen) auftreten (Kaiser & Schulze, 2015;Metzing-Blau & Schnepp, 2008). Im Vergleich zu Kindern ohne Pflegeaufgaben kann sich diese Chancenungleichheit negativ auf die Entwicklung der betroffenen Kinder und Jugendlichen auswirken und eine zukünftige soziale Teilhabe verhindern (Aldridge & Becker, 1993;Bjorgvinsdottir & Halldorsdottir, 2014;Kaiser & Schulze, 2015;Metzing-Blau & Schnepp, 2008).…”
Section: Schritt: Bestimmung Der Voraussetzungen Und Folgenunclassified